Oral history and production of documents and knowledge in history of science - Kamensky, Andrea Paula dos Santos Oliveira (Circumscribere International Journal for the History of Science, 2016)
The present paper approaches the relationships among history, orality and science by discussing the procedures proper to oral history relating to the production of knowledge in history of science, particularly as concerns the construction of new historical sources for the understanding of the processes of specialization and institutionalization of science in Brazil. I approach this subject by considering oral history an indispensable resource in the taping of oral and/or audiovisual records containing the life stories of scientists who contributed to the institutionalization of chemistry in Brazil, as well as several interdisciplinary fields of knowledge that consolidated based on chemistry. Based on interviews with chemists I intend to assess, from the perspective of individuals active in the Brazilian scientific community, how the construction of knowledge, specialties, new research fields and institutions occurs.